Glutamatergic system: Another target for the action of porphyrinogenic agents - Lavandera, J V; Fossati, M; Azcurra, J; Batlle, A; Buzaleh, A M (Cellular and Molecular Biology, 2015)
The N-methyl-diethyl-aspartate (NMDA) receptor has been reported to play an important role in several acute and chronic neuropathologic syndromes. 5-aminolevulinic acid (ALA) accumulates in acute porphyrias due to a deficiency in the heme biosynthetic pathway. Considering that glutamate uptake inhibition caused by ALA could be one of the reasons conducing to porphyric neuropathy, it was of interest to evaluate the effect of porphyrinogenic agents on NMDA glutamatergic system. To this end receptor levels and apparent affinity (Kd) were analyzed in mice brain cortex and cerebellum. NMDA levels were diminished after chronic Isoflurane anaesthesia in brain cortex. In cerebellum, a diminution was observed after acute Enflurane and Isoflurane and allylisopropylacetamide, while ethanol administration showed a significant increase. ALA administration diminished NMDA levels only in cerebellum. Affinity constant was only reduced in brain cortex after chronic Isoflurane treatment. In conclusion, glutamatergic system appears to be involved in the action of some of the porphyrinogenic drugs studied mainly in cerebellum. Receptors regulation should therefore be considered an important mechanism in the cellular response to specific drugs, with the aim of designing new therapies and elucidating the mechanisms leading to porphyric neuropathy and acute attack triggering.